DESIGN AND CONSTRUCTION OF RENOGRAPH FOR RENAL FUNCTION TEST USING CsI(Tl) DETECTOR AND MICROCONTROLLER AT89C51 - -, Setyadi; Isaris, Rill (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2007)
The development of Renograph prototypes for renal function testing has been initiated in BATAN since 1983, five generation prototypes using NaI(Tl) Scintillation de-tector have been successfully constructed and utilized in hospitals. Due to the new re-gulation for human safety, then the use of low energy radioisotopes with shorter half life time should be considered. It requires to develop the new instrument of higher sensitivity and better performances. This paper presents design of renograph using CsI(Tl) scintillation as a new type detector and a 16 bits Microcontroller AT89C51 as the data processor for renal function test, so renograph with a high reliable and better performances in application is achie-ved. The use of CsI(Tl) and Microcontroller as the data processor is the development made from the previous prototypes, the system is also provided with a serial commu-nication facility to Personal Computer through serial-port RS 232. Static examination to the pulses generated by a Function Generator with fre-quency up to 12.000 Hz and the dynamic test using 137Cs and 60Co radiation sources have been carried out successfully. The non-linearity integral of the system shows the response is linear up to frequency of 65.000 Hz with strong correlation coefficient, that is R2 ~ 0,9999. The calculation of the statistical feasibility counting to the both CsI(Tl) detector equipments for the two sources above with confidence level of 0,95 give the Ï‡2 are 0.238 and 0.078. These are much smaller than the Ï‡2 value in the table, that is 0.711 for N = 5. Hence, the modified renograph system using CsI(Tl) and Microcontroller AT89C51 has good counting linearity and fulfills the counting feasibility statistically.